PENGARUH PENDIDIKAN, PENGANGGURAN DAN KETIMPANGAN GENDER TERHADAP KEMISKINAN DI SUMATERA UTARA - Alfi Amalia (Universitas Islam Negeri Sumatera Utara, 2017)
This study aims to be able to know the influence of education, unemployment, and gender inequality on poverty in the province of North Sumatra. The population mentioned is the population of 33 districts / cities in North Sumatra from 2010-2013. The data sources used in this research is secondary data in the form of a period (time series) in the period 2010-2013. The data obtained from various sources such as the Central Bureau of Statistics (BPS) of North Sumatra province, journals, and research results. In this research used a research method that is research library (Library Research) is used in this research through library materials such as books, literature, scientific writings, and reports relating to the topic under study. Data collection techniques used is to perform direct recording of data in the form of t ime series ie 2010-2013. Results showed that the F-statistic of 36.147 and the value of statistical probability .000000 it states that education, unemployment and gender inequality together affect the poverty in North Sumatra, while the remaining 36.14% is not described in this study. And education and gender inequality variables a significant and negative effect on poverty while unemployment variables significant and positive impact on poverty in North Sumatra.